PENGARUH PEMBERIAN EKSTRA ETHANOL DAUN TITHONIA DIVERSIFOLIA, EKSTRA ALLIUM SATIVUM dan CAMPURAN EKSTRA ALLIUM SATIVUM TERHADAP KERUSAKAN HISTOLOGI GINJAL dan HATI MENCIT HIPERGLIKEMIA - Eka p F; Sukarjati M.Kes (WAHANA, 2018)
Tithonia diversifolia and allium sativum are believed by the community to lower blood sugar levels. Research on safety test of Tifonia diversifolia extract and Allium sativum to histology of liver and kidney has not been done. The purpose of this research was to find out the effect of trimonic diversifolia extract extract and Allium extract as well as the extract and the second leaf mixture to histology structure of kidney and liver of mice with diabetes.This study was an experimental study in 45 mice sampled in divided into 11 groups of control groups extract tithonia diversifolia 50 mg / kg bb ,100 mg / kgbb and 150 mg / kg bb. As well as Alium sativum extract 50 mg / kg bb 100 mg / kgbb and 150 mg / kg bb and mixed extract of tithonia diversfolia and Allium sativum C2 25:25 mg / kgbb, C3 50:50 mg / kg bb And 75:75 mg / kg bb. And administration of chlamydial gliben. The extract was administered for 35 days, after which surgery and preparation of histology of kidney and liver of mice Furthermore, the result he analyzed using spss Anova one way and descriptive analysis The results of this study showed no significant differences in the control group (P = 1,000), Treatment of Tithonia diversifolia extract Dose 50mg / kgbb (P = 1.00), dose 100mg / kgbb (P = 1.00), dose 100mg / kgbb (P = 1.00) Dose 150m / kgbb (P = 1.00) Kgbb (P = 1.00) and mixed dosage 25: 25mg / kgbb (0.111) but significant with 50:50 mixed significantly differentiated doiss treatments (P = 0.003) and C4 mixture extract (0.000) on liver histology On histology of the liver. While on the histology of the kidney,perlakuan Ekstrak Tithonia diversifolia dosis 50mg/kgbb,dosis 100 mg/kgbb,150mg/kgbb serta perlakuan esktrak Allium sativum dosis 50mg/kgbb,dosis 100 mg/kgbb150mg / kgbb also extracts Tithonia diversifolia mixture and Allium sativum extract dose 25:25 mg / kgbb 50:50 dose and 75:75 does not affectthe histology of renal mice Conclusion: There is a mild hemorrhage to the liver in all treatments of tithonia extract, Allium sativum, or mixture. Keywords:Tithonia diverifolia,Allium Sativum,Histologic of hepar and kidney of mice